"Don't eat me/eat me"-combined apoptotic body analogues for efficient targeted therapy of triple-negative breast cancer. Issue 40 (22nd September 2021) - Zhang, Kailong; Fu, Huanru; Xing, Chao; Luo, Yi; Cheng, Fangfang; Fu, Qiang; Huang, Yujie; Qiu, Longxin
Abstract : Apoptotic body analogues have successfully inherited the anti-phagocytosis ("don't eat me") and specific homologous targeting ("eat me") capacities from parent cells. Abstract : For the purpose of efficient targeted therapies, suppressing phagocytosis by a mononuclear phagocyte system (MPS), enhancing the "active" targeted delivery, and meeting clinical production criteria are extremely critical for engineering strategies of novel drug delivery systems. Herein, we used a chemically-induced membrane blebbing and extrusion combined method to induce triple-negative breast cancer (TNBC) cell apoptosis to secrete apoptotic body analogue (ABA) vesicles on a large scale for therapeutic drug delivery. After optimization, the ABAs have a desirable size, good biocompatibility, and long-term colloidal stability. Furthermore, ABAs present anti-phagocytosis ("don't eat me") and specific homologous targeting ("eat me") capacities because of their inheritance of membrane proteins such as CD47 and cellular adhesion molecules from parent cells. After loading with toxic protein saporin and anti-twist siRNA, ABAs can significantly inhibit the growth and lung metastasis of TNBC in an orthotopic metastasis model due to their reduced clearance of immune organs, long circulation time, and enhanced targeted accumulation at the tumor sites. These results suggest the great potential of ABAs for targeted drug delivery therapy, in particular efficient TNBC treatment.